Etnobiologi Tumbuhan Sebagai Bahan Baku Tas Noken Oleh Suku Yali di Distrik Abenaho Kabupaten Yalimo, Papua - Yemeus Helakombo; Rosye H.R. Tanjung; Suharno Suharno (Jurnal Biologi Papua, 2022)
Noken is a typical Papuan bag or container made from plant organs such as bark, roots, etc. The purpose of this study was to determine the plant species used as raw materials for noken making in District of Abenaho, Yalimo Regency, Papua. The research conducted during the period of January–April 2021. The methods used were field surveys and interview. Observations were made in Hulhule Village, Abenaho District, and involving 60 respondents. The results showed that there were 8 types of plant species used as raw materials for making noken. Those were Boehmeria nivea, B. platylla, B. penduliflora, Boehmeria sp., and Pipturus dentatus, while three (3) other types used as natural dyes were: Merei (Bixa orellana), Turmeric (Curcuma domestica) and Senggani (Melastoma polyanthum). Noken processing in Hulhule Village is done by weaving/knitting and spun manually by hand. The spinning process is carried out after the coloring process.Key words: plant; fiber; noken; Yalimo